Early Carcinogenesis Involves the Establishment of Immune Privilege via Intrinsic and Extrinsic Regulation of Indoleamine 2,3-dioxygenase-1: Translational Implications in Cancer Immunotherapy - Holtzhausen, Alisha; Zhao, Fei; Evans, Kathy S.; Hanks, Brent A. (Frontiers in Immunology, 2014)
Although prolonged genetic pressure has been conjectured to be necessary for the eventual development of tumor immune evasion mechanisms, recent work is demonstrating that early genetic mutations are capable of moonlighting as both intrinsic and extrinsic modulators of the tumor immune microenvironment. The indoleamine 2,3-dioxygenase-1 (IDO) immunoregulatory enzyme is emerging as a key player in tumor-mediated immune tolerance. While loss of the tumor suppressor, BIN-1, and the over-expression of cyclooxygenase-2 have been implicated in intrinsic regulation of IDO, recent findings have demonstrated the loss of TβRIII and the upregulation of Wnt5a by developing cancers to play a role in the extrinsic control of IDO activity by local dendritic cell populations residing within tumor and tumor-draining lymph node tissues. Together, these genetic changes are capable of modulating paracrine signaling pathways in the early stages of carcinogenesis to establish a site of immune privilege by promoting the differentiation and activation of local regulatory T cells. Additional investigation of these immune evasion pathways promises to provide opportunities for the development of novel strategies to synergistically enhance the efficacy of the evolving class of T cell-targeted “checkpoint” inhibitors.